A revisit to the effect of annealing temperature on magnetic properties of LaFe0.5Mn0.5O3. (25th March 2019) - Dutta, Uma; Ghosh, Debamalya; Haque, Ariful; Kumar, Lalit; Mandal, Tapas Kumar; Walke, Pravin S; Pal, Kamalesh; Gayen, Arup; Kundu, Asish K; Seikh, Md Motin
Abstract: We report an experimental study for the structural and magnetic properties of highly pure LaFe0.5 Mn0.5 O3 perovskite phase. The impurity free LaFe0.5 Mn0.5 O3 has been prepared by sol-gel technique at 500 °C and annealed at different temperatures up to 1000 °C. Previous works on LaFe0.5 Mn0.5 O3 revealed presence of secondary phases along with contradicting magnetic properties. Such as, Bhame et al (2005 Phys. Rev . B72 054426–7) reported the superparamagnetic or spin-glass like behavior for 200 °C treated sample that persisted even at 700 °C sample. However, Wei et al (2012 Mater. Chem. Phys .136 755–61) claimed room temperature ferromagnetism in all the samples annealed in the range of 600 °C–700 °C where the saturation magnetization decreases with the increase in temperature. These contradicting results lead us to revisit the effect of annealing temperature on the magnetic properties of LaFe0.5 Mn0.5 O3 . We noticed a gradual increase in magnetization with increase in annealing temperatures without any signature of long range spin ordering for pure single phase samples. The increased magnetic moment with annealing temperatures has been attributed to the suppression of surface contribution of disordered spin. The low temperature magnetic behaviors can be explained by the interacting cluster glass behavior for the pristine as well as for 1000 °C annealed samples.